Urban and agriculturally influenced water contribute differently to the spread of antibiotic resistance genes in a mega-city river network. (1st July 2019) - Wu, Dong; Su, Yinglong; Xi, Hui; Chen, Xinyuan; Xie, Bing
Abstract: The widespread of water borne antibiotic resistance genes (ARGs) represents a growing threat to the health of millions of people. Our study detected the relative abundances of 10 ARG subtypes in the Shanghai river network, where the major ARG components were strB, sul1, and ermB . These ARGs were significantly enriched by the combined sewage, tail water from urban wastewater treatment plant and runoff from agricultural areas, which reached the Suzhou (SZ), Dianpu (DP), and Huangpu (HP) River, respectively (one-way ANOVA, P  < 0.01). The target ARGs were distributed in varying patterns across different rivers. bla CTX-M and bla TEM contributed to the increase of total ARGs in the rivers influenced by urban sources, particularly in the SZ River, whose distribution of ARGs was significantly related to that of the confluence of the whole river network (Mantel test, P  < 0.01). The bacterial community was closely structured with ARGs and potential pathogenic bacteria's association with target ARGs became significant in downstream samples (Procrustes test, P  = 0.03). Water near urban wastewater fallouts was observed to have the highest content of intl1 in the DP River, whose downstream samples' intl –ARG relationship fitted the same regression model as that of the network confluence ( R  = 0.84, P  < 0.001). The amelioration of river water quality does not reduce ARGs, but may affect their distributional patterns in the river network in Shanghai. Graphical abstract: Image 1 Highlights: ARGs in combined sewage mostly related to their distribution in the downstream. WWTP facilitated the HGT of ARGs to the downstream. Bacterial community related to different types of ARGs in different rivers. ARGs and pathogens became closely associated in downstream river networks. Amelioration of water quality may not reduce ARGs in the river network.